PENGERTIAN, PENYEBAB, PENCEGAHAN DAN PENANGGULANGAN PENYAKIT AKIBAT KERJA (Literatur Review) - Dian Safitri; Rangga Perdana; Ajely Rani Marlina; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2023)
Occupational Disease is a disease or health condition caused by work routine or work environment. Occupational diseases can be caused by various factors, for example from the work itself, the work process, the work tools used, the work environment and also the materials used for work. Occupational diseases can be caused by: physical, chemical, biological, ergonomic, and psychosocial factors. The prevention efforts in the hospital work environment include occupational health for employees, sanitation in the hospital environment, patient safety, visitors and hospital staff and others.